THE MODERATING EFFECT OF FAMILY VALUE ON THE INFLUENCE OF PURPOSE DRIVEN, FINANCIAL DRIVEN, AND FEELING VALUE ON EMPLOYEE RETENTION IN THE JAKARTA DIGITAL INDUSTRY - Muhamad Akmal; Frans Assa; Rudolf Lumbantobing (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The demographic bonus can be a big advantage in Indonesia but it can also be a disaster if not managed properly. As is known, in this global era which is increasingly integrated with the internet, the use of human resources will be increasingly streamlined with the use of the internet or other technology. Therefore, it will be a challenge for the millennial generation to compete for jobs. Meanwhile, the challenge for the company itself is managing millennials, who are often considered the most disloyal generation. Employee retention is critical in achieving and maintaining organizational success. Employees with rich experience are believed to make significant contributions to the organization (Tian et al., 2020). As a result, organizations must pay attention to human resource policies to retain employees and reduce turnover. An employee leaving may require coworkers to take care of tasks for the missing person and additional work, which can lead to higher rates of absenteeism, stress, and lower performance, The industrial revolution 4.0 has had a huge impact on companies. Competition in the industrial world is increasingly competitive, providing its own challenges for companies to manage employees, so they can compete with other companies. Because it cannot be denied that employees have a very important role in the sustainability and future development of the company. In a company, competitive advantage is determined and driven by Human Resources (HR).